Improving speaking skill using mingle game - Susilawati; Fitri Novia; Rekha Asmara (Language and Education Journal, 2021)
This study aimed to consider whether there was a significant difference in speaking skill between students who were taught using the Mingle game and those who were not.This research was conducted using a quasi-experimental design. The sample consisted of two groups: X MIPA 2 (experimental group) and X MIPA 3 (control group), which were chosen using a purposive sampling process. The data was collected using an oral test.The t-test was used to evaluate the results. The outcome of the independent sample t-test indicated that tobtained (3.96) was higher than the critical value of ttable (1.99), indicating that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) accepted. It was determined that there was a significant difference in speaking ability between students who were taught using the Mingle game and those who were not.